Clinical Insights About Topical Treatment of Mild-to-Moderate Pediatric and Adult Atopic Dermatitis. Issue 3 (May 2019) - Lynde, Charles W.; Bergman, James; Fiorillo, Loretta; Guenther, Lyn; Keddy-Grant, Jill; Landells, Ian; Marcoux, Danielle; Ramien, Michele; Rehmus, Wingfield
Atopic dermatitis (AD) is a chronic inflammatory skin condition, also referred to as atopic eczema, that is identified by itching and recurrent eczematous lesions. It often starts in infancy where it affects up to 20% of children but is also highly prevalent in adults. AD inflicts a significant psychosocial burden on patients and their families and increases the risk of other immune-mediated inflammatory conditions, such as asthma and allergic rhinitis, food allergy, and mental health disorders. It is a lifelong condition associated with epidermal barrier dysfunction and altered immune function. Through the use of emollients and anti-inflammatory agents, current prevention and treatment therapies attempt to restore epidermal barrier function. Acute flares are treated with topical corticosteroids. Topical calcineurin inhibitors (TCIs) and topical corticosteroids (TCSs) are used for proactive treatment to prevent remission. There remains a need and opportunity to improve AD care through future research directed toward an improved understanding of the heterogeneity of the disease and its subtypes, the role of autoimmunity in its pathogenesis, the mechanisms behind disease-associated itch and response to specific allergens, and the comparative effectiveness and safety of therapies.